Hubungan Antara Pola Asuh Orang Tua Dengan Perilaku Merokok Remaja Laki-Laki Kelas 11 Di SMAN Demak - Dhani Luthfi Hakim; Wigyo Susanto; Dwi Heppy Rochmawati (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Risky behavior that commonly emerges during adolescence is cigarette smoking, which has detrimental effects on adolescents’ health and overall development. The increasing prevalence of smoking among individuals aged 10–18 years highlights the need for closer attention to the factors influencing this behavior. One important factor is parenting style, as it plays a crucial role in shaping character, instilling discipline, and strengthening adolescents’ capacity for self-regulation. This study employed a cross-sectional design, in which the independent variable (parenting style) and the dependent variable (smoking behavior) were measured simultaneously. The sample consisted of 128 male eleventh-grade students at SMAN Demak. Data were analyzed bivariately using the Gamma correlation test, a nonparametric statistical method appropriate for ordinal-scale variables. The Spearman Rank test yielded a p-value of 0.000 (p < 0.05), indicating a statistically significant relationship between parenting style and smoking behavior among male adolescents. The Gamma correlation coefficient of −0.630 indicates a strong negative association, suggesting that more positive parenting styles are associated with lower tendencies to smoke. These findings confirm that positive and supportive parenting practices may serve as an important protective factor in preventing adolescents’ involvement in smoking behavior.